Renewing our hope : essays for the new evangelization - Barron, Robert, 1959- (The Catholic University of America Press, 2020)
"With Renewing Our Hope: Essays for the New Evangelization, Bishop Barron traces the need of the renewal of the Catholic Church through four stages: "Renewing Our Mission," regaining confidence to share the Catholic faith by looking to the Church's intellectual inheritance; "Renewing Our Minds," examining that inheritance more closely, including Thomas Aquinas, Hans Urs von Balthasar, John Henry Newman, and Pope Francis; "Renewing the Church," overcoming sexual abuse and strengthening the priesthood and family life; and "Renewing Our Culture," judgments on politics, society, and art. Bishop Barron demonstrates again in this book his ability to make the fruits of his wide reading accessible to a broad audience, while still giving his academic colleagues much to consider. Includes a bibliography and index of subjects and names"--